(untitled) (Sciences & Technologie. B, Sciences de l’ingénieur, 2005)
An accurate design of both rectangular and circular patch antenna on a micro strip substrate is applied by using the moments method, an efficient technique to dyadic Green’s function is presented, in order to show the feasibility of the method some numerical data are generated, the effects of different parameters on the directivity are discussed, comparative study between this two different shapes is done and compared with other computed results.